Clinical characterization of a novel alpha1-antitrypsin null variant: PiQ0Heidelberg - Maria A. Presotto; Martina Veith; Frederik Trinkmann; Kai Schlamp; Markus Polke; Ralf Eberhardt; Felix Herth; Franziska C. Trudzinski (Respiratory Medicine Case Reports, 2022)
The clinical characterization of a null variant of SERPINA1 – PiQ0Heidelberg – resulting in alpha1-antitrypsin (AAT) deficiency is described. This rare mutation (c.-5+5 G > A) has been previously identified but not clinically described. The 77 year-old female patient had GOLD-3, Group B COPD, severe destructive panlobular emphysema and newly observed respiratory failure on exertion at the time the genetic analysis was performed. Serum AAT level was 0.1 g/L (reference 0.9–2.0 g/L). Isoelectric focusing showed only the Z-protein indicating that this was a null mutation. The patient has started AAT replacement. Early screening and identification of AAT deficiency would allow for earlier intervention.